Global Development Finance, 1998 Country Tables and Analysis and Summary Tables (Washington World Bank Publications Mitcham, VIC, Australia Central Book Services New Zealand [Distributor], 1999)
Annotation Global Development finance 1999 (GDF) is the most comprehensive and detailed publication available on developing countries' external debt and financial, flows. This year's GDF devotes special emphasis to the continuing impact of the financ ial crisis on private and official flows to the developing world.
Trade
Keywords: Development Banks; Economics, International